2017
DOI: 10.1042/bsr20160505
|View full text |Cite
|
Sign up to set email alerts
|

Association between IL-13 +1923C/T polymorphism and asthma risk: a meta-analysis based on 26 case-control studies

Abstract: Asthma is a serious and hereditary respiratory disorder affecting all age groups. Interleukin-13 (IL-13) is a central regulator of allergic inflammation. The purpose of the present study was to estimate the relationship between IL-13 +1923C/T polymorphism and asthma susceptibility. Relevant case-control studies published between January 2000 and July 2016 were searched in the online databases. Review Manage (RevMan) 5.3 was used to conduct the statistical analysis. The pooled odds ratio (OR) with its 95% confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
1
11
3
1
Order By: Relevance
“…In line with these findings, we presume IL-13 +2044 A/G and IL-4 -590 C/T polymorphisms maybe potential susceptible predictor for pediatric asthma. However, some studies showed that IL-13 -1112C/T and +1923C/T polymorphisms were correlated with increased risk of asthma in children, [ 68 , 69 , 71 ] which is different from our results. The reasons may be as follows: on the one hand, a significantly increased risk between IL-13 -1112C/T and asthma risk was observed by Liu et al [ 68 ] in overall populations, but not in Asians or Chinese.…”
Section: Discussioncontrasting
confidence: 99%
“…In line with these findings, we presume IL-13 +2044 A/G and IL-4 -590 C/T polymorphisms maybe potential susceptible predictor for pediatric asthma. However, some studies showed that IL-13 -1112C/T and +1923C/T polymorphisms were correlated with increased risk of asthma in children, [ 68 , 69 , 71 ] which is different from our results. The reasons may be as follows: on the one hand, a significantly increased risk between IL-13 -1112C/T and asthma risk was observed by Liu et al [ 68 ] in overall populations, but not in Asians or Chinese.…”
Section: Discussioncontrasting
confidence: 99%
“…In line with these ndings, we presume IL-13 + 2044 A/G and IL-4 -590 C/ T polymorphism maybe risk factors in pediatric asthma. However, some studies has shown that IL-13 -1112C/T and IL-13 + 1923C/T variant were correlated with increased risk of asthma in children 58,59,61 , which is different from our results. The reasons may be the following: a signi cantly increased risk between IL-13 -1112C/T and asthma risk was observed by Liu et al 58 in overall populations, but not in Asians.…”
Section: Sensitivity Analysis and Publication Biascontrasting
confidence: 99%
“…Polymorphisms in IL-6 [68], IL-4 [69], high-affinity IgE receptor [70], IL-4R [71], disintegrin and metalloproteinase 33 [72], and IL-13 [73] have been associated with epithelial dismantling and malfunctioning, especially in the context of asthma and chronic obstructive pulmonary disease [74,75]. In this sense, a high level of IL-13 in asthmatic patients has been involved in wall remodeling processes [76,77].…”
Section: Airway Epithelium As a Key Player In Orchestrating The Allermentioning
confidence: 99%